The Effect of Family Business Succession Preparation and Implementation on Post Succession Performance: Evidence from Steel Industry in Thailand - Yongvongphaiboon, Permsin; Aryupong, Mayuree (Siam University Journal of Business Administration, 2022)
This research paper examined the important factors affecting the succession preparation, the implementation plan, and post-succession performance of the family business in steel industry in Thailand. The important factors were perceived potential, perceived commitment, and perceived capability of the successor. The objective of the research was to examine the relationship between the three factors, succession preparation, implementation, and the post-succession performance of the family-owned steel firms in Thailand. A total of 169 questionnaires were collected from the top and middle managers which had gone through a leadership transition from 30 steel firms located in Bangkok, Samutsakorn, or Samutprakarn. These areas have a large number of steel business owners. The results indicated that all three factors had impact on the effectiveness of the succession preparation with perceived capability having the highest impact. The results also showed that the succession preparation, succession implantation, and the post-succession performance were positively related. This research paper provided an insightful outlook on how important the effects of succession preparation and implementation were on family-owned steel business in Thailand as succession issues impacted by the global business environment with increased volatility.